Karakteristik respon siswa dalam menyelesaikan soal geometri berdasarkan taksonomi solo - Permatadewi, Chairunnisa Dian (Rekarta Academic Publisher, 2018)
This qualitative descriptive study aims to determine the ability of students responses in solving geometry problems in terms of SOLO Taxonomy. There are 5 stages of SOLO Taxonomy, namely structural, unstructural, multistructural, relational, and expanded abstract. Subjects in this study were taken by purposive sampling technique and obtained 3 students of class VIII A at Salatiga Pangudi Luhur Middle School. Data collection techniques were carried out using test and interview methods. Data analysis techniques include data reduction, data presentation, and conclusion drawing. Based on the results of the study obtained by 66% of students are in the relational stage, and 33% are able to reach the expanded abstract stage